2022
DOI: 10.1155/2022/2555647
|View full text |Cite
|
Sign up to set email alerts
|

Highly Expressing SCARA5 Promotes Proliferation and Migration of Esophageal Squamous Cell Carcinoma

Abstract: Background. Thrombospondin type 1 domain-containing 7A (THSD7A) was reported to play a procancer role in esophageal squamous cell carcinoma (ESCC). The aim of the study was to screen the downstream functional genes of THSD7A and explore their functions in ESCC, based on the reported research into THSD7A function and on gene microarrays. Methods. We adopted quantitative reverse-transcription polymerase chain reaction (qRT-PCR) and Celigo high-content screening (HCS) technology to screen the downstream genes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Since its invention, gene microarray has been utilized extensively in scientific research, the biopharmaceutical industry, and medical diagnostics. By using gene microarrays technology, Zhumai et al discovered that scavenger receptor class A member 5 (SCARA5) was a downstream driver of thrombospondin type 1 domain‐containing 7A (THSD7A) in esophageal squamous cell carcinoma (ESCC), and SCARA5 could promote the proliferation and migration of ESCC cells 22 . Cai et al used protein and gene microarrays to compare wild‐type (WT) and drug‐resistant (DR) Pseudomonas aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its invention, gene microarray has been utilized extensively in scientific research, the biopharmaceutical industry, and medical diagnostics. By using gene microarrays technology, Zhumai et al discovered that scavenger receptor class A member 5 (SCARA5) was a downstream driver of thrombospondin type 1 domain‐containing 7A (THSD7A) in esophageal squamous cell carcinoma (ESCC), and SCARA5 could promote the proliferation and migration of ESCC cells 22 . Cai et al used protein and gene microarrays to compare wild‐type (WT) and drug‐resistant (DR) Pseudomonas aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…By using gene microarrays technology, Zhumai et al discovered that scavenger receptor class A member 5 (SCARA5) was a downstream driver of thrombospondin type 1 domain‐containing 7A (THSD7A) in esophageal squamous cell carcinoma (ESCC), and SCARA5 could promote the proliferation and migration of ESCC cells. 22 Cai et al used protein and gene microarrays to compare wild‐type (WT) and drug‐resistant (DR) Pseudomonas aeruginosa. The results showed that there were 679 mutation sites in the DR Group, and the drug resistance rate of cefoperazone sodium/sulbactam sodium remained high from 2013 to 2015.…”
Section: Introductionmentioning
confidence: 99%
“…They also stated that SCARA5 promotes the proliferation and migration of ESCC cells and that SCARA5 is expressed differently between ESCC and normal esophageal tissue. However, they did not find any significant association between SCARA5 expression and clinicopathological parameters or prognosis [ 31 ]. There is also evidence that SCARA 5 directly interacts with FAK.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jumai et al reported scavenger receptor class A member 5 (SCARA5) to be the downstream gene of THSD7A in esophageal squamous cell carcinoma (ESCC) [ 31 ]. Not much is known about SCARA5.…”
Section: Introductionmentioning
confidence: 99%
“…However, its effects on ESCC proliferation and migration are contradictory and need to be confirmed by further studies [67]…”
Section: Iron Metabolism In Escc With Ferroptosismentioning
confidence: 98%